2017
DOI: 10.1007/978-1-4939-7306-4_1
|View full text |Cite
|
Sign up to set email alerts
|

The A-Like Faker Assay for Measuring Yeast Chromosome III Stability

Abstract: The ability to rapidly assess chromosome instability (CIN) has enabled profiling of most yeast genes for potential effects on genome stability. The A-like faker (ALF) assay is one of several qualitative and quantitative marker loss assays that indirectly measure loss or conversion of genetic material using a counterselection step. The ALF assay relies on the ability to count spurious mating events that occur upon loss of the MATα locus of haploid Saccharomyces cerevisiae strains. Here, we describe the deployme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…To test CIN on endogenous chromosomal markers, and extend this to include the dis3 E729K allele, we measured instability of chr III using the A-like faker (ALF) assay that measures loss of the native MAT locus [31,32]. We observed a significant increase in the frequency of ALF colonies for both dis3-ts and dis3 E729K ( Figure 5(a,b)).…”
Section: The Dis3 E729k Allele Alters Cell Cycle Progression In the Cmentioning
confidence: 99%
See 2 more Smart Citations
“…To test CIN on endogenous chromosomal markers, and extend this to include the dis3 E729K allele, we measured instability of chr III using the A-like faker (ALF) assay that measures loss of the native MAT locus [31,32]. We observed a significant increase in the frequency of ALF colonies for both dis3-ts and dis3 E729K ( Figure 5(a,b)).…”
Section: The Dis3 E729k Allele Alters Cell Cycle Progression In the Cmentioning
confidence: 99%
“…While it is unclear why CIN rates are this high in dis3-EXO, we note that this allele completely ablates the exonuclease activity and shows slow growth at all tested temperatures, whereas dis3-ts and dis3 E729K only show strong growth defects at temperatures above 34°C. ALF phenotypes can reflect multiple forms of CIN, including whole chromosome loss, local deletions or chromosome arm loss, and gene conversion [31,32]. One mechanism of CIN in RNA processing mutants that could lead to an ALF phenotype is the accumulation of DNA:RNA hybrids in genomic DNA called R-loops [33].…”
Section: The Dis3 E729k Allele Alters Cell Cycle Progression In the Cmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not detect enhanced benomyl sensitivity in yhc1-1 using this assay, possibly because of limited allelic penetrance at 30°C. By quantifying the rate of endogenous chromosome III loss using the A-like faker assay (Novoa et al, 2018) in the single and double mutants at permissive temperature of 25°C, we found a dramatic synergy between disruption of SNU114 or HSH155 and loss of the SAC ( Figure 3C ). Recurrently, yhc1-1 phenotype was not enhanced, consistent with the lack of benomyl sensitivity under the same conditions and likely a limitation of the ts-allele.…”
Section: Resultsmentioning
confidence: 99%
“…Growth curves were conducted in a Tecan M200 plate reader and compared using the area under the curve as previously described (Chang et al, 2017). The CTF and ALF assays were performed as described (Novoa et al, 2018; Stirling et al, 2011). For plasmid loss, strains carrying pRS313::HIS3 were grown overnight in SC-histidine, then plated on YPD and allowed to form colonies without selection before replica plating onto SC-histidine.…”
Section: Methodsmentioning
confidence: 99%